An experimental Customer Satisfaction Index to evaluate the performance of city logistics services - Paddeu, Daniela; Fancello, Gianfranco; Fadda, Paolo (Transport, 2017)
Freight transport in urban areas entails benefits (i.e. free access to goods when needed), but also negative externalities (environmental, social and transportation impacts). In response to these problems, the concept of city logistics emerged, for the purpose of planning, organizing, coordinating and controlling physical and information flows in order to find a compromise between efficient freight distribution in urban areas and protection of the environment. A typical city logistics initiative is the Urban Freight Consolidation Centre (UFCC), the benefits of which are significant. Its financial issues though represent a huge problem for public administrations. However, a large customer network, comprising retailers participating in the initiative, could make the UFCC a self-financing scheme. The key to expanding the scheme is closely linked with marketing campaigns and customer care. Therefore, customer care analysis represents an important tool in developing UFCC schemes. In this paper, a new Customer Satisfaction Index (CSI) is proposed for evaluating UFCC service quality. The new index, named CSImod, is a modified version of the traditional CSI, but places greater emphasis on customer dissatisfaction, so as to analyse the most critical areas of the service with a view to improving them. The index has been tested using experimental data collected within the CIVITAS RENAISSANCE Project, in which the Bristol and Bath Freight Consolidation Centre (BBFCC) scheme was evaluated. The evaluation was done from a user perspective, i.e. the participating retailers. The CSImod places more importance on the most dissatisfied customers making it possible to understand why they are dissatisfied and with what. Thus, it is possible to intervene with the aim of improving those areas of the service that are perceived as the worst. In spite of the high level of satisfaction with the overall service provided by the BBFCC, thanks to the CSImod the analysis pointed out that some retailers are dissatisfied with the delivery time arrangements and also with deliveries that were getting wet, issues about which the BBFCC manager was totally unaware. The CSImod could be used by UFCC operators to extend the network of the retailers involved and could therefore provide an implicit solution for making the scheme self-financing. First published online: 29 Feb 2016